THE STUDY OF THE WORKS OF A RUBAI POET (Eureka Journal of Education & Learning Technologies, 2026)
The following article provides information on the manuscripts of Amir Khusrow Dehlavi’s heritage, especially the manuscripts stored at the Institute of Oriental Studies named after Abu Rayhan Biruni under Academy of Sciences of the Republic of Uzbekistan, and their research on rubai's. The manuscript that we have reviewed shows the origin of the ghazals. However, no mention is made of where ruba’is came from. The order of giving of the ruba’is is not based on any principle in many manuscripts. It can be seen that only a few of them are in alphabetical order, either by the first letter of ruba’i, or by the last letter of the rhyme. It is worth noting that the mixed circulation of the ruba’is of the five devans in the manuscript may be attributed to the long-standing tendency of the poet's devotees to try to fit into one collection.
Keywords: Ruba’i, manuscript, source studies, artistic heritage.